361 SMOKING CESSATION AMELIORATES PROGRESSION FROM EARLY TO ADVANCED TYPE 2 DIABETIC NEPHROPATHY. Issue 1 (1st January 2007) - Phisitkul, K.; Chuahirun, T.; Hudson, C.; Simoni, J.; Wesson, D. E.
Abstract : Purpose: To determine if smoking cessation ameliorates progression from early (microalbuminuria) to advanced (macroalbuminuria) nephropathy due to type 2 diabetes mellitus (DM2). Methods: We recruited 92 subjects with DM2, 39 nonsmokers and 52 smokers, all with microalbuminuria defined as urine albumin (mg)-to-creatinine (g) ratio (alb/cr) 20 to 200 mg/g in a spot am specimen. Smokers underwent a 12-week smoking cessation intervention, including nicotine patch, oral bupropion, and weekly substance abuse counseling. Eleven of the 52 smokers successfully quit (21%). Therefore, three groups were compared: nonsmokers (NS, n = 39), smokers who continued smoking (S, n = 41), and smokers who quit (Quit, n = 11). All subjects were prescribed angiotensin-converting enzyme inhibitors (ACEI) and then followed for 5 years with yearly measurements of urine alb/cr and plasma creatinine for estimated GFR (eGFR). Results: There was no difference in initial urine alb/cr among the three groups. After ACEI, urine alb/cr was lower in NS (18.7 ± 4.0) than S (34.7 ± 4.7) and Quit (29.7 ± 4.7), p = .045. At 5 years, urine alb/cr was higher in S (99.2 ± 13.3) than NS (21.2 ± 1.8) and Quit (23.9 ± 2.3), p < .001. Seven of the 41 S subjects developed macroalbuminuria (urine alb/cr > 200 mg/g), but none of the NS or Quit subjects did. Five-year eGFR was not different among groups. Conclusions: The data show that despite ACEI, continued smoking promotes progression of DM2 nephropathy as measured by increasing urine alb/cr. Furthermore, the risk of nephropathy progression in DM2 after smoking cessation is comparable to that of nonsmokers. The data support the contention that smoking cessation ameliorates progression from early to advanced DM2 nephropathy.